HIV infected adults do not have an excess of colonising bacteria in their large airways - Zijlstra Eduard E; Phiri Amos; Wilson Lorna; Musaya Janelisa; Gordon Stephen B; Molyneux Malcolm E (BMC Infectious Diseases, 2003)
Abstract Background HIV infected adults have increased susceptibility to bacterial pneumonia but the underlying immune defect is poorly understood. We tested the hypothesis that HIV infection might be associated with increased bacterial colonisation of distal airways by nasal flora, which would then predispose patients to bacterial pneumonia. Methods Healthy volunteer adults with normal chest radiographs were recruited. Bronchoscopy was carried out and uncontaminated mucosal samples were collected from proximal and distal sites in the large airways using a protected specimen brush. Samples were cultured to detect typical respiratory tract colonising organisms, and the proportion of samples found to contain colonising bacteria compared between HIV infected and uninfected subjects using non-parametric tests. Results Forty-nine subjects were studied of whom 27 were HIV infected. Colonising bacteria were identified in the nasopharynx of all subjects including Streptococcus pneumoniae in 6/49 subjects (5 HIV uninfected). Colonising bacteria were found in the distal airway of 6 subjects (3/27 HIV infected vs 3/22 HIV uninfected ; χ2 = 0.07, p = 0.8). Streptococcus pneumoniae was identified in the trachea of all subjects with nasal colonisation but in the distal airway of only 1 subject. Conclusions There was no evidence to support a hypothesis of increased airway bacterial colonisation in healthy HIV infected subjects.